2011
DOI: 10.1093/jac/dkr441
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent potentiation of the pro-inflammatory functions of human neutrophils by tigecycline in vitro

Abstract: Tigecycline, by functioning as a Ca(2+) ionophore, and independent of antimicrobial activity, potentiates the pro-inflammatory functions of human neutrophils in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…These properties include the ability to block microglial activation and consequent pro‐inflammatory cytokine release as well as inhibition of matrix metalloproteinases and actions on GABA A and NMDA receptors (Ahmadirad et al., ; Lee et al., ; Wang et al., ; Yan et al., ). Tigecycline, unlike other tetracyclines, has calcium ionophore activity, which could also potentially mediate a suppression of convulsions (Cockeran et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These properties include the ability to block microglial activation and consequent pro‐inflammatory cytokine release as well as inhibition of matrix metalloproteinases and actions on GABA A and NMDA receptors (Ahmadirad et al., ; Lee et al., ; Wang et al., ; Yan et al., ). Tigecycline, unlike other tetracyclines, has calcium ionophore activity, which could also potentially mediate a suppression of convulsions (Cockeran et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have demonstrated effective properties of minocycline (second‐generation semisynthetic tetracycline derivative) in the formalin (Cho et al., ) and surgically‐induced neuropathic pain models (Padi and Kulkarni, ), the novel analgesic properties of tetracycline‐like compounds need to be investigated further, especially if tigecycline, or a derivative, is to become an important AUD treatment. In addition to their antimicrobial actions, tetracyclines have been shown to have anti‐inflammatory actions (Cockeran et al., ; Domercq and Matute, ), although these effects have not been investigated for tigecycline. However, the drug is known to have excellent tissue penetration and unappreciable metabolism; unchanged drug is found in the feces, with minor secondary glucuronidation and renal elimination (Meagher et al., ).…”
mentioning
confidence: 99%
“…Unlike macrolides that accelerate neutrophil apoptosis and impair neutrophil migration (23), a previous study showed that TGC penetrates neutrophils and maintains their intracellular concentration for a relatively long time. Besides, it enhances the proliferation and proinflammatory activities of neutrophils in vitro (9).…”
Section: White Blood Cell Indicesmentioning
confidence: 99%
“…Previous studies showed harmful effects of TGC on the immune system. It was found to penetrate neutrophils and stimulate their proliferation and cytotoxicity by acting as a calcium ionophore, thus augmenting the innate response (9). However, it could have a suppressive effect on antibodies produced by lymphocytes (10).…”
Section: Immunomodulatory Effects Of Tigecycline In Balb/c Micementioning
confidence: 99%